Deaf Signers’ Processing of the Sentence: An Indicator of Their Specific Pathway to the Written Word? - Marie Périni; Adrien Dadone; Brigitte Garcia (Languages, 2024)
This article addresses the issue of access to the written word for deaf people whose main language is sign language. We question the status of sentence processing in the acquisition of a written language by deaf people, visual beings par excellence. This written language is both the written form of another language (namely a vocal language) and another modality, that of writing (as opposed to the oral form of language i.e., the face-to-face form of language), which they have not experienced in their own, non-written language. We highlight two points in the literature that we feel are crucial to addressing this issue: first, the significant linguistic distance between their L1 (SL) and their L2 (written vocal language), which severely limits the possibility of positive transfer from one to the other; and secondly, the evidence of a cognitive functioning specific to deaf people, marked in particular by higher processing capacities in the visual domain. Based on the results of two studies on the written output of deaf people, we suggest that particularities in the acquisition of the sentence are closely linked both to the structure of SL and to the visual functioning of this population. Finally, we emphasize the importance of using sign language as a metalanguage in teaching writing to deaf signers.